2001
DOI: 10.2343/geochemj.35.355
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous distribution of dissolved organic carbon in the Sea of Japan.

Abstract: Dissolved organic carbon (DOC) in the Sea of Japan was determined by the high temperature catalytic oxidation (HTCO) method. The chemical parameters related to DOC, i.e., the three-dimensional excitation-emission matrix spectrum, nutrients, chlorophyll a, dissolved oxygen and monosaccharides concentration were also determined. The vertical distribution of DOC in the northernmost sampling site (CM10; 44.1°N, 138.6°E) was not like that those in other sampling sites. An anomalously high DOC concentration was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…2). Though EEM-PARAFAC was firstly applied for the JSPW in the present study, similar vertical distributions of FDOM H were previously observed in the Japan Sea by measuring the fluorescence intensities at a single pair of excitation (320 nm) and emission (420 nm) wavelengths3438 and by using EEM33. In the western North Pacific, the amounts of FDOM H -1 and FDOM H -2 were also lowest in the surface waters, followed by an increase with depth that peaked at 1000–1500 m and then decreased slightly with depth (Fig.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…2). Though EEM-PARAFAC was firstly applied for the JSPW in the present study, similar vertical distributions of FDOM H were previously observed in the Japan Sea by measuring the fluorescence intensities at a single pair of excitation (320 nm) and emission (420 nm) wavelengths3438 and by using EEM33. In the western North Pacific, the amounts of FDOM H -1 and FDOM H -2 were also lowest in the surface waters, followed by an increase with depth that peaked at 1000–1500 m and then decreased slightly with depth (Fig.…”
Section: Resultssupporting
confidence: 63%
“…Though only a few studies have clarified the distributional patterns of DOM in the Japan Sea, it was reported that DOC concentrations in the JSPW were higher than those in deep waters of the North Pacific 33 . Such high levels of DOC are possibly due to transport of semi-labile DOC from surface layers 1 along with the JSPW formation.…”
mentioning
confidence: 99%
“…The potential temperatures in deep water below 2000 m are almost constant at 0.06–0.1°C from the Japan Basin to the southern Yamato Basin, although higher temperatures occur in the surface layer at 18.4–26.9°C. Several studies related to this cruise have been reported for hydrographic data, dissolved oxygen, nutrients, tritium [ Gamo , 1999; Gamo et al , 2001], dissolved organic carbon [ Yamaguchi et al , 2001], silver [ Zhang et al , 2001], and cadmium [ Abe , 2005] in the Sea of Japan. Those studies reflect the unique features of the Sea of Japan's marine geochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, 3D-EEMs is an effective method for the characterization of fluorescent organic matter in sea water. Fluorescent organic matter which seems to be refractory organic substances is present in the deep layer of the Pacific Ocean (Hayase and Shinozuka, 1995;Yamaguchi et al, 2001;Nakaguchi et al, 2003). 3D-EEMs were measured by using the same samples which were collected by the R/V Hakuho-Maru KH-02-4 cruise.…”
Section: The Relationship Between Organic Selenide and Fluorescent Ormentioning
confidence: 99%
“…The analytical procedure for 3D-EEMs has been described elsewhere (Yamaguchi et al, 2001). Only a brief description is given here.…”
Section: D-eems Analysismentioning
confidence: 99%